Leaf Endophytes of Populus trichocarpa Act as Pathogens of Neighboring Plant Species - Newcombe, George; Fraser, Shannon J.; Ridout, Mary; Busby, Posy E. (Frontiers in Microbiology, 2020)
The conventional definition of endophytes is that they do not cause disease, whereas pathogens do. Complicating this convention, however, is the poorly explored phenomenon that some microbes are endophytes in some plants but pathogens in others. Black cottonwood or poplar (Populus trichocarpa) and wheat (Triticum aestivum) are common wild and crop plants, respectively, in the Pacific Northwest USA. The former anchors wild, riparian communities, whereas the latter is an introduced domesticate of commercial importance in the region. We isolated Fusarium culmorum – a well known pathogen of wheat causing both blight and rot – from the leaf of a black cottonwood tree in western Washington. The pathogenicity of this cottonwood isolate and of a wheat isolate of F. culmorum were compared by inoculating both cottonwood and wheat in a greenhouse experiment. We found that both the cottonwood and wheat isolates of F. culmorum significantly reduced the growth of wheat, whereas they had no impact on cottonwood growth. Our results demonstrate that the cottonwood isolate of F. culmorum is endophytic in one plant species but pathogenic in another. Using sequence-based methods, we found an additional 56 taxa in the foliar microbiome of cottonwood that match the sequences of pathogens of other plants of the region. Overall, our results suggest that plants can host a diverse group of pathogens of other plants in their community, raising questions about the role of apparent competition in plant community dynamics.